Correlated One Site Three Dimensions VHF Broadband Digital Interferometer algorithm and Phased Array Radar (PAR) Observations - Elbaghdady, Lotfy; Ushio, Tomoo; Allam, Ahmed; Kawasaki, Zen; Ragab, Mohamed (Journal of Atmospheric Electricity, 2014)
Broadband radio interferometers have been developed to locate the sources of VHF/UHF radiation from lightning discharges in three spatial dimensions (3D) and time. In a previous work, a VHF broadband digital interferometer has been used to estimate the 3D lightning location from only one site. In order to study the accuracy of this algorithm, a cross check of one site 3D VHF broadband digital interferometer with Phased Array Radar (PAR) system will be introduced in this paper. In August 18, 2012, VHF pulses from lightning flashes have been recorded by VHF digital broadband interferometer LIB site located in Nara, Japan. On the same day the precipitation profile has been recorded using Phased Array RADAR (PAR) located in Osaka University. The 3D locations of four flashes are compared with the PAR horizontal and Range-Height Indicator RHI scan images. This comparison introduced a good correlation between 3D VHF broadband digital interferometer algorithm and the precipitation profiles recorded by PAR.